Targeting Metabolism as a Platform for Inducing Allograft Tolerance in the Absence of Long-Term Immunosuppression - Cheng, Chih-Hsien; Lee, Chen-Fang; Oh, Byoung Chol; Furtmüller, Georg J.; Patel, Chirag H.; Brandacher, Gerald; Powell, Jonathan D. (Frontiers in Immunology, 2020)
Transplant tolerance in the absence of long-term immunosuppression has been an elusive goal for solid organ transplantation. Recently, it has become clear that metabolic reprogramming plays a critical role in promoting T cell activation, differentiation and function. Targeting metabolism can preferentially inhibit T cell effector generation while simultaneously promoting the generation of T regulatory cells. With this in mind, we hypothesized that costimulatory blockade with CTLA4-Ig in combination with targeting T cell metabolism might promote the induction of tolerance.